DETERMINANTS OF BUDGET ABSORPTION MODERATED BY WORK PLAN AND ORGANIZATIONAL COMMITMENT - Maharani, Apsari; Handoyo, Sarwo Edy (Graduate Program of Universitas Tarumanagara, 2025)
This research aims to examine the influence of budget planning and procurement of goods and services on budget absorption, with work plans and organizational commitment as moderators in the Directorate General of Intellectual Property (DGIP) of the Ministry of Law and Human Rights, Republic of Indonesia. By analyzing the data on budget absorption gathered between 2019 and 2022, it can be noted that the absorption rate has consistently decreased over these years and has not achieved full utilization, remaining below 100% annually. This trend in government budget absorption is prevalent across Indonesia, with a slow start at the beginning and acceleration toward the end of the fiscal year (Oktaliza Y., 2020). The decrease in DGIP's budget absorption has led to a reduction in the provision of intellectual property services to stakeholders. Therefore, it is necessary to examine several variables that influence budget absorption, including budget planning, procurement of goods and services, and organizational commitment, as identified in previous studies. This research adds the variable of work plans as a moderating factor, which has not been explored before. The study employed a questionnaire method administered to 30 selected respondents, comprising officials and employees of DGIP. The sample consisted of individuals involved directly in the processes of work and budget planning, procurement of goods and services, and budget absorption. The data were analyzed using quantitative methods and processed using Statistical Package for the Social Sciences (SPSS) version 27. The findings of this research indicate that budget planning and procurement of goods and services have a positive and significant impact on budget absorption within the DGIP of the Ministry of Law and Human Rights. Additionally, work plans moderate the influence of budget planning and procurement of goods and services on budget absorption. However, organizational commitment does not moderate the impact of budget planning and procurement of goods and services on budget absorption in the DGIP of the Ministry of Law and Human Rights.